Gender, household behavior, and rural development - Doss, Cheryl; Quisumbing, Agnes R. (International Food Policy Research Institute, 2021)
Our understanding of decision-making within rural households has changed substantially since interest in intrahousehold decision-making emerged in the 1980s. Conventional wisdom, rooted in the unitary theory of the household, held that households are groups of individuals who have the same preferences and fully pool their resources (Becker 1981). Accumulating empirical evidence has shifted this concept of the household in which households decide “as one” to a “collective” model in which individual household members may have different preferences, may not completely pool resources, and may bargain over outcomes in both production and consumption (Haddad, Hoddinott, and Alderman 1997).